2015
DOI: 10.4103/2229-516x.149235
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus seroprevalence and its correlation with CD4 cells and liver enzymes among human immunodeficiency virus positive individuals at a tertiary care hospital in North-West India

Abstract: Background:Human immunodeficiency virus (HIV) and hepatitis B virus (HBV) are global health concerns. Due to shared routes of transmission, co-infection is common. Their co-existence can cause severe liver complications and immunological impairment in infected individuals.Aim:To find the prevalence of HBV co-infection in HIV patients and to assess the pattern of liver enzymes and CD4 T-cell counts in HIV monoinfected and HIV/HBV co-infected patients.Materials and Methods:A total of 342 consecutive confirmed HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…For the vaccination, the first dose is often given at 6 weeks of age. This prevalence variation according to the age groups was also documented in other studies in Africa [Diop‐Ndiaye et al, ] and Asia [Hooja et al, ], with, respectively, 25.3 and 36.7%, which showed a high prevalence, respectively, in patients aged from 30 to 40 and 18 to 38 years. The main routes of transmission in different countries might explain the prevalence variation in the different age groups [Saravanan et al, ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For the vaccination, the first dose is often given at 6 weeks of age. This prevalence variation according to the age groups was also documented in other studies in Africa [Diop‐Ndiaye et al, ] and Asia [Hooja et al, ], with, respectively, 25.3 and 36.7%, which showed a high prevalence, respectively, in patients aged from 30 to 40 and 18 to 38 years. The main routes of transmission in different countries might explain the prevalence variation in the different age groups [Saravanan et al, ].…”
Section: Discussionsupporting
confidence: 85%
“…This information could explain the higher prevalence of HBV/HIV coinfection in African countries compared to developed countries. As demonstrated by others studies [Attia et al, ; Hooja et al, ], the prevalence of HBV/HIV coinfection was higher in males than females but this difference was not statistically significant ( P = 0.245). Although being not statistically significant, the prevalence of HBV/HIV was higher in patients aged over 40 ( P = 0.181) and lower in patient aged under 20 years.…”
Section: Discussionmentioning
confidence: 58%
“…Specifically, the mean serum ALT level of HIV/HBV coinfected patients was significantly higher than that of HIV mono-infected patients (p = 0.002), similar to studies carried out in Ghana [29] and France [30]. Likewise, the mean AST level of HIV/HBV coinfected patients was significantly higher than that of HIV-mono-infected patients in line with a study reported in Northern India [31], but it was contrary to the findings of a study in Nigeria [32]. In HIV-positive patients, the increase in hepatic enzymes could be secondary to multiple factors such as alcoholism, lipid-lowering drugs, antibiotics, coinfection with hepatotropic viruses or opportunistic infections, and direct hepatic damage caused by HIV [33].…”
Section: Discussionsupporting
confidence: 89%
“…These controversial results may be partly due to the differences in the immune status of the study participants or it may be due to the viral hepatitis. A study by Hooja et al (2015) also proved that HIV infection may accelerate the progression of hepatic complications.…”
Section: Discussionmentioning
confidence: 94%